Studi Eksperimental Penggunaan Abu Ampas Tebu dan Limbah Karbit sebagai Material Subtitusi Semen pada Campuran Beton - Adam Creflo Rombe; Frans Phengkarsa; Lisa Febriani (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
Research on construction technology continues to be developed with the aim of utilizing carbide waste and bagasse ash as a substitute for cement in the manufacture of normal quality concrete. The purpose of this study was to determine the value of testing the compressive strength, split tensile strength and flexural strength with substitute materials from carbide waste and sugarcane ash 0%, 4%, 8% and 12%. The American concrete method was used in the manufacture of test objects. institute (ACI). The test is carried out when the concrete has passed the maintenance period of 7, 21 and 21 days. From the results of this study, the compressive strength values ​​of concrete at 28 days of age with variations of 10% carbide waste and 0%, 4%, 8% and 12% bagasse ash were 26.044 MPa, 16.042 MPa, 14.626 MPa and 14.248. The split tensile strength test results with 10% waste and 0%, 4%, 8% and 12% bagasse ash were 2.288 MPa, 1.77 MPa, 1.533 MPa and 1.486 MPa. The results of the flexural strength test with a variation of waste 10% and bagasse ash 0%, 4%, 8% and 12% were 3.030 MPa, 2.568, 2.414 and 2.362. The results of this study indicate that the higher the addition of carbide waste and bagasse ash, the lower the compressive strength, split tensile strength and flexural tensile strength of concrete.